Instructional Support for Self-Development Activities: Teaching Hair Oil Application to Students with Mild Intellectual Disabilities - Hellen Nita Fazrin; Lilis Suwandari (CV. AFDIFAL MAJU BERKAH, 2026)
Teaching self-care skills to students with mild intellectual disabilities requires structured, repetitive, and individualized instruction. This study aimed to explore the abilities of third-grade students with mild intellectual disabilities in performing a grooming task applying hair oil as part of a self-development learning program. Using a qualitative case study design, data were collected through in-depth interviews, participatory observation, and document analysis involving three students and one teacher at a special school in Cirebon Regency. The findings revealed that while students were able to follow basic grooming steps, they faced consistent challenges in memory retention, task sequencing, and motor coordination. Emotional responses such as frustration and disengagement were also observed when difficulties occurred. The teacher's use of task analysis, modeling, verbal prompting, and positive reinforcement proved effective in supporting student performance and engagement. This study highlights the importance of individualized, emotionally responsive instruction in life skills education and suggests that even simple grooming tasks can contribute significantly to students’ independence and self-esteem